Effects of Greater rhea (Rhea americana) female attributes on egg viability - Lábaque, María Carla (2019)
We conducted a study throughout a breeding season in a captive-bred population of Greater rheas (Rhea americana) to evaluate the association between egg viability and the female´s body weight and age. A total of 180 eggs laid by 15 females of three age classes (5 individuals per class) were collected, individually identified, and their morphometric traits, fertility and hatchability were registered. Egg fertility increased with female´s age but was unaffected by female weight. Hatching rate does not correlate with maternal attributes. The current paper contributes towards understanding the role of certain maternal attributes in egg viability. Our findings suggest that breeding Greater rheas in large flocks where free mating occurs, increases the expression of natural sexual behavior and enhances the productivity and welfare of the birds.